2009
DOI: 10.1136/emj.2008.064865
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the complicated neutropenic fever in the emergency department

Abstract: Objectives:The purpose of this study was to identify independent factors that can be used to predict whether febrile neutropenic patients who appear healthy at presentation will develop subsequent complications, using variables that are readily available in the emergency department (ED).Method:The medical records of 192 episodes in which the patients presented to the ED with neutropenic fever resulting from chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…C‐reactive protein was reported to be useful for aiding treatment‐related decision‐making, and it was suggested that high CRP levels are associated with sepsis and microbiologically documented infections in patients with febrile neutropenia . However, it was subsequently reported that CRP is not very specific and hence is a poor diagnostic marker of infection in patients with febrile neutropenia .…”
Section: Discussionmentioning
confidence: 99%
“…C‐reactive protein was reported to be useful for aiding treatment‐related decision‐making, and it was suggested that high CRP levels are associated with sepsis and microbiologically documented infections in patients with febrile neutropenia . However, it was subsequently reported that CRP is not very specific and hence is a poor diagnostic marker of infection in patients with febrile neutropenia .…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al . aimed to predict complicated febrile neutropenia in the ED, finding that laboratory parameters such as platelet count, CRP, and pulmonary infiltration as revealed by chest x‐ray readily identified patients most likely to develop complications . CRP, an indicator of inflammation, is sensitive in predicting febrile neutropenia, especially in the presence of shock and hematologic malignancies .…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to undertake subgroup analysis for primary studies due to mixed patient groups data not being analysed separately (e.g. solid tumour and haematological malignancy data were combined) …”
Section: Resultsmentioning
confidence: 93%
“…The included studies comprised of four prospective and three retrospective cohort studies. Three studies analysed data according to repetitive episodes of FN, whereas the remainder analysed by study population. These studies were conducted in 20 countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation